Three Centuries of Conflict in East Timor - Kammen, Douglas (Rutgers University Press, 2021)
One of the most troubling but least studied features of mass political violence is why mass violence often recurs in the same place over long periods of time. Douglas Kammen explores this pattern in Three Centuries of Conflict in East Timor, studying East Timor’s tragic past, and focusing on the small district of Maubara. This book combines an archival trail and rich oral interviews to reconstruct the history of the leading families of Maubara from 1712 until 2012.